Identification of miR-128 Target mRNAs That Are Expressed in B Cells Using a Modified Dual Luciferase Vector - Schreiber, Sandra; Daum, Patrick; Danzer, Heike; Hauke, Manuela; Jäck, Hans Martin; Wittmann, Jürgen (Biomolecules, 2023)
MicroRNAs (miRNAs) are 21–25 nucleotide long non-coding ribonucleic acids that modulate gene expression by degrading transcripts or inhibiting translation. The miRNA miR-128, originally thought to be brain-specific, was later also found in immune cells. To identify a valuable immune cell model system to modulate endogenous miR-128 amounts and to validate predicted miR-128 target mRNAs in B cells, we first investigated miR-128 expression using Northern blot analysis in several cell lines representing different stages of B cell development. The results showed that only primary brain cells showed significant levels of mature miR-128. To study the function of miR-128 in immune cells, we modified dual luciferase vectors to allow easy transfer of 3′ UTR fragments with predicted miR-128 binding sites from widely used single to dual luciferase vectors. Comparison of in silico predicted miR-128-regulated mRNAs in single and dual luciferase constructs yielded similar results, validating the dual luciferase vector for miRNA target analysis. Furthermore, we confirmed miR-128-regulated mRNAs identified in silico and in vivo using the Ago HITS-CLIP technique and known to be expressed in B cells using the dual luciferase assay. In conclusion, this study provides new insights into the expression and function of miR-128 by validating novel target mRNAs expressed in B cells and identifying additional pathways likely controlled by this miRNA in the immune system.
CRIS-Team Scopus Importer:2023-11-03
Keywords: B cells; dual luciferase assay; HITS-CLIP; microRNA; miR-128; miRNA prediction algorithm